ANALISIS PENGARUH KADAR AIR DAN CAMPURAN FENOL TERHADAP TEGANGAN TEMBUS MINYAK KEMIRI SUNAN SEBAGAI PERTIMBANGAN MINYAK ISOLASI ALTERNATIF - Ardiansyah, Muhammad Doni; Dhofir, Moch.; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
This thesis discusses the enhancement of the dielectric strength of sunan candlenut oil by using phenol additives so that it can be used as an alternative liquid insulation for high voltage equipment. The increase in breakdown voltage level was achieved by adding various mixtures of phenol. Purification through heating was carried out to reduce the water content in the sunan candlenut oil. Electrical testing (breakdown voltage test circuit), physical testing (water content testing using the oven method), as well as calculating conductivity values (by measuring leakage current using a DC circuit) and permittivity (using an LCR multimeter) were conducted. These tests were performed to determine the feasibility of sunan candlenut oil as an insulating oil. The test results showed that the breakdown voltage of pure sunan candlenut oil was 11.67 kV/2.5mm, which did not meetthe SPLN 49 standard of 1982, which is 30kV/2.5mm. The addition of phenol successfully increased the breakdown voltage to 61.91 kV/2.5 mm, and with heating, it reached 67.27 kV/2.5mm. The highest breakdown voltage of 67.27 kV/2.5mm was obtained by mixing 8% phenol (32 ml) and heating the sunan candlenut oil simultaneously. The test results of relative permittivity showed values of pure sunan candlenut oil and 8% phenol-added sunan candlenut oil as 9.89 and 10.25, respectively. In the conductivity test, the values for pure sunan candlenut oil and 8% phenol-added sunan candlenut oil were 22,6×10−9 S/m and 21,6×10−9 S/m,respectively. It can be concluded that the addition of phenol can inhibit the occurrence of breakdown voltage and maintain oil stability, while heating can reduce the water content from 900 ppm to 596.7 ppm. In terms of water content, the modified sunan candlenut oil does not yet meet the maximum standard allowed by SPLN 1982, which is ≤30 ppm. However, in terms of breakdown voltage, the modified sunan candlenut oil has met the SPLN 49 standard of 1982, which is 30 kV/2.5 mm. Keyword: Phenol, water content, insulating oil, kemiri sunan oil, breakdown voltage. conductivity, relative permittivity